Metafictional poetics of Victor Pelevin’s novel “iPhuck 10” - Бабай, Павло Миколайович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article analyzes the ways of artistic realization of the aesthetic-reflective metafictional complex in Victor Pelevin’s novel “iPhuck 10”. The metanarrative structure of the novel is traced, which is built with the use of a special type of narrator - a literary simulator, which at the same time is the sum of all the cultural forms of writing, a kind of archive thesaurus, on the other hand undermines the basis of its own narrative by exposing the empty nature and the existential problematic nature of the narrative. Metatextual issues are updated at the level of the deictic structures of the language-speech that are basic for aesthetic communication. A further subject of study is the method of isomorphic conjugation of plot-motive event dynamics with semantics of a series of ecstatically described and interpreted art objects of various medial-semiotic nature. Thanks to the dual function of the diegetic narrator as the subject of the story and its object, the equivalence effect of different metalanguages and discourses is simultaneously created within the framework of the basic conceptual metaphors and symbolic constructions of the novel. Thanks to this, we can talk about both metanarrativeness and the metafiction of the poetics of the novel. Metafictional reflection productively correlates with author’s anthropological concepts. In particular, the plot of the creator-impostor combines the through Pelevinian motive of suffering and pain as the fundamental characteristics of human life with pain as an inalienable quality and source of creativity. A software algorithm is grown as a conscious person to create works of art, and its creators reinforce sorrow, anxiety, and the experience of the meaninglessness of existence so that creativity is genuine. Man is experienced by the temptation of demiurgy, by meeting with the Other, by the demand for personal self-transcendence. Thus, the author succeeds in isomorphically combining metafictional poetics and existential anthropology of the novel.